Protease-Activated Receptor-2 Deficiency Attenuates Atherosclerotic Lesion Progression and Instability in Apolipoprotein E-Deficient Mice - Zuo, Pengfei; Zuo, Zhi; Zheng, Yueyue; Wang, Xin; Zhou, Qianxing; Chen, Long; Ma, Genshan (Frontiers in Pharmacology, 2017)
Inflammatory mechanisms are involved in the process of atherosclerotic plaque formation and rupture. Accumulating evidence suggests that protease-activated receptor(PAR)-2 contributes to the pathophysiology of chronic inflammation on the vasculature. To directly examine the role of PAR-2 in atherosclerosis, we generated apolipoprotein E(ApoE)/PAR-2 double-deficient mice. Mice were fed with high-fat diet for 12 weeks starting at ages of 6 weeks. PAR-2 deficiency attenuated atherosclerotic lesion progression with reduced total lesion area, reduced percentage of stenosis and reduced total necrotic core area. PAR-2 deficiency increased fibrous cap thickness and collagen content of plaque. Moreover, PAR-2 deficiency decreased smooth muscle cell(SMC) content，macrophage accumulation，matrix metallopeptidase(MMP)-9 expression and neovascularization in plaque. Relative quantitative PCR assay using thoracic aorta revealed that PAR-2 deficiency reduced mRNA expression of inflammatory molecules, such as vascular cell adhesion molecule(VCAM)-1, intercellular adhesion molecule(ICAM)-1, tumor necrosis factor(TNF)-α and monocyte chemoattractant protein(MCP)-1. In vitro experiment, we found that PAR-2 deficiency reduced mRNA expression of interferon(IFN)-γ, interleukin(IL)-6, TNF-α and MCP-1 in macrophage under unstimulated and lipopolysaccharide(LPS)-stimulated conditions. These results suggest that PAR-2 deficiency attenuates the progression and instability of atherosclerotic plaque.